Emerging Sexual Ethics and the Erosion of African Ethos - Besong, Eric Ndoma (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
The emerging sexual ethics that characterise the contemporary society, remains new to Africa, a phase of the erosion of African ethos, and a negation of the sacredness and classical norms of sex, which deserves to be addressed by all and sundry. It is a contemporary trend brought to fore by homosexuals, bisexuals and transsexuals, among which are the radical feminists, who indoctrinate many with the practice and continuously push very hard for legalisation and acceptance by all cultures and religions. But interestingly, many cultures and religions still remain opposed to the practice and its evolved ethics since they abuse human sexuality and African ethos. Clearly, adherents and feminists of the ill-practices with the new sex ethics have lost touch with moral sanity and the metaphysical Being, God. Only worthwhile cultural traits need be borrowed into and imbibed by other cultures in contact. The rising ugly development can best be addressed through strong opposing legislations, the sustenance of cultural and moral norms and values (ethics) and attitudinal change.